Comparison of Different Surgical Approaches for Treating Aortic Graft Infections - Xia, Yu; Sun, Lizhong; Jian, Kaitao; Peng, Hao; Lin, Yi; Liu, Wei (The Thoracic and Cardiovascular Surgeon, 2024)
Background There is still no guideline or consensus on the treatment of aortic graft infection. This study reported and compared conservative and surgical treatment and different surgical methods for aortic graft infection.Methods Data from aortic graft infections treated at our institution between February 2017 and June 2022 were retrospectively analyzed. Clinical data and surgical approaches were evaluated.Results This article retrospectively analyzed the treatment and prognosis of 48 patients (43 males) with aortic graft infection. The patients were divided into conservative treatment group (n = 15) and surgical treatment group (n = 33). During follow-up, the mortality rate of the conservative treatment group was significantly higher than that of the surgical treatment group (p < 0.05). The survival curve also showed that the survival time of the surgical treatment group was longer than that of the conservative treatment group (p < 0.05). The surgical treatment group included local treatment (n = 5), in situ replacement (n = 8), and bypass surgery (n = 20) groups. There was no significant difference in the mortality rate at 1 month or final follow-up among the local treatment, in situ replacement, and bypass surgery groups.Conclusion Surgical treatment is the optimal option for treating aortic graft infections compared to conservative treatment.
Keywords: aortic graft infection; surgical treatment; conservative treatment; mortality